2012
DOI: 10.1111/j.1949-8594.2012.00140.x
|View full text |Cite
|
Sign up to set email alerts
|

Calculator Use on NAEP: A Look at Fourth‐ and Eighth‐Grade Mathematics Achievement

Abstract: This article summarizes research conducted on calculator block items from the 2007 fourth-and eighth-grade National Assessment of Educational Progress Main Mathematics. Calculator items from the assessment were categorized into two categories: problem-solving items and noncomputational mathematics concept items. A calculator has the potential to be used as a problem-solving tool for items categorized in the first category. On the other hand, there are no practical uses for calculators for noncomputational math… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
0
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 7 publications
1
0
0
Order By: Relevance
“…Through the calculator-assisted approach, they were more able to notice the whole problem-solving process and to interpret their answers. These results might confirm that the presence of a calculator provides a richer learning environment to foster low-achievers' learning number sense, as well as to remove the need of focusing on counting procedures and providing a powerful understanding of symbols (Walcott & Stickles, 2012). Inasmuch as the evidence that the calculator-assisted instruction could help low-achievers develop number sense, it might be reasonable to infer that the calculator-assisted teaching approach would also be advantageous to high-or middle-achievers.…”
Section: Discussionsupporting
confidence: 69%
“…Through the calculator-assisted approach, they were more able to notice the whole problem-solving process and to interpret their answers. These results might confirm that the presence of a calculator provides a richer learning environment to foster low-achievers' learning number sense, as well as to remove the need of focusing on counting procedures and providing a powerful understanding of symbols (Walcott & Stickles, 2012). Inasmuch as the evidence that the calculator-assisted instruction could help low-achievers develop number sense, it might be reasonable to infer that the calculator-assisted teaching approach would also be advantageous to high-or middle-achievers.…”
Section: Discussionsupporting
confidence: 69%
“…When implemented in the classroom, digital math tools such as basic calculators, graphing calculators, and computer algebraic systems (CAS) can enhance student achievement. Research comparing assessment scores of students who did and did not use calculators has shown that students who reported calculator use outperformed those who reported no calculator use (Walcott & Stickles, 2012). Similar results were demonstrated in Schmidt et al's (2009) study, concluding that a majority of students who learned using CAS technology did noticeably better on assessments when compared to students who knew without CAS.…”
Section: Introductionsupporting
confidence: 62%
“…Previous studies in which large-scale assessment data were used showed that students who used calculators for mathematics problem solving items had significantly higher test scores than the students who did not use them (Mullis et al, 2021: Walcott & Stickles, 2012.…”
Section: Discussionmentioning
confidence: 96%
“…For some item types, an onscreen calculator should not be provided depending on the construct being measured and for some items the calculators may not be needed. For instance, Walcott and Stickles (2012) conducted a study using eighth grade level NAEP data that included two types of itemsproblem solving items and noncomputational mathematics concept items-where they studied the effect of calculator use and item types. The results showed that students who used calculators had significantly better performance on problem solving items when compared to students who did not use calculators.…”
Section: On-screen Calculators As a Technological Innovationmentioning
confidence: 99%